Sistem Ekonomi Kerakyatan dalam Globalisasi Perekonomian - Bhudianto, Wahyu - (Transformasi, 2012)
AbstractRegional economic development is a process by which local governments andcommunities to manage resources - resources and form a partnership with local government ,private sector to create a new jobs and stimulate the development of economic activity (economicgrowth) in the region. . Regional economic development is a process that includes the formationof new institutions, the development of alternative industries, improvement of existing workforcecapacity to produce better products and services, identifying new markets, transfer of knowledgeand technology, and development efforts new.In the current era of regional autonomy, the concept of community economic developmentsystem must be translated into operational programs based on the domestic economy at thecounty level and city with a high degree of independence. It should be emphasized that thedevelopment of community economic system in the current era of regional autonomy should notbe interpreted in a territorial perspective, but should be developed in the perspective ofregionalization in which it is integrated in the potential unity, excellence, opportunity, social andcultural character. the Populist economic system should be able to empower local communitiesand improve the Regional Economic Development.Keywords: Globalization, Populist , The economic system